Group education for adolescents with type 1 diabetes during transition from paediatric to adult care: study protocol for a multisite, randomised controlled, superiority trial (GET-IT-T1D). Issue 11 (11th November 2019) - Mok, Elise; Henderson, Melanie; Dasgupta, Kaberi; Rahme, Elham; Hajizadeh, Mohammad; Bell, Lorraine; Prevost, Melinda; Frei, Jennifer; Nakhla, Meranda
Abstract : Introduction: Transition from paediatric to adult care is challenging for adolescents and emerging adults (ages 18 to 30 years) with type 1 diabetes (T1D). This transition is characterised by a deterioration in glycaemic control (haemoglobin A1c (HbA1c)), decreased clinical attendance, poor self-management and increased acute T1D-related complications. However, evidence to guide delivery of transition care is lacking. Given the effectiveness of group education in adult diabetes glycaemic control and improvements in qualitative measures in paediatric diabetes, group education is a potentially feasible and cost-effective alternative for the delivery of transition care. In emerging adults with T1D, we aim to assess the effectiveness of group education visits compared with usual care on HbA1c, T1D-related complications, psychosocial measures and cost-effectiveness after the transfer to adult care. Methods and analysis: In a multisite, assessor-blinded, randomised, two-arm, parallel-group, superiority trial, 212 adolescents with T1D (ages 17 years) are randomised to 12 months group education versus usual T1D care before transfer to adult care. Visits in the active arm consist of group education sessions followed by usual T1D care visits every 3 months. Primary outcome is change in HbA1c measured at 24 months. Secondary outcomes are delays in establishing adult diabetes care, T1D-related hospitalisations and emergency department visits, severe hypoglycaemia, stigma, self-efficacy, diabetes knowledge, transition readiness, diabetes distress, quality of life and cost-effectiveness at 12 and 24 months follow-up. Analysis will be by intention-to-treat. Change in HbA1c will be calculated and compared between arms using differences (95% CI), along with cost-effectiveness analysis. A similar approach will be conducted to examine between-arm differences in secondary outcomes. Ethics and dissemination: The study was approved by McGill University Health Centre Research Ethics Board (GET-IT/MP-37-2019-4434, version 'Final 1.0 from November 2018). Study results will be disseminated through peer-reviewed publications. Trial registration number: NCT03703440 .